PENGARUH METODE PETA KONSEP BERBASIS ONLINE TERHADAP MOTIVASI DAN HASIL BELAJAR IPA KONSEP GAYA SISWA KELAS IV SD (JS (JURNAL SEKOLAH), 2023)
Abstract: The Influence of the Online Concept Map Method in Science Learning the Concept of Style on Motivation and Learning Outcomes in Fourth Grade Students of SD Negeri Mangasa Makassar. Supervised by Muhiddin and Syarifuddin Kune. This study aims to determine the effect of the Concept Map method on learning motivation and learning outcomes of fourth grade students at SD Negeri Mangasa Makassar. This research was conducted at SD Negeri Mangasa Makassar in the academic year 2020/2021. Data analysis was done descriptively and inferentially. Descriptively obtained: (1). The average student motivation is 80.15 with a standard deviation of 6.23 in the High category of 19% and the Medium category of 91%. (2) Student learning outcomes have increased from pretest to posttest with a gain value of 0.57 with a frequency distribution of 27% in the High category, 70% in the Medium category and 3% in the Low category (3) Then the inferential results show a significant value for the results of hypothesis testing smaller than the value of the significance level of 0.05 where 0.00